Branched-Chain Amino Acid Catabolism Impacts Triacylglycerol Homeostasis in Chlamydomonas reinhardtii. Issue 4 (6th February 2019) - Liang, Yuanxue; Kong, Fantao; Torres-Romero, Ismael; Burlacot, Adrien; Cuine, Stéphan; Légeret, Bertrand; Billon, Emmanuelle; Brotman, Yariv; Alseekh, Saleh; Fernie, Alisdair R.; Beisson, Fred; Peltier, Gilles; et al.
Abstract : The degradation of branched-chain amino acids provides carbon precursors for lipid biosynthesis during nitrogen starvation and ATP for lipid remobilization upon nitrogen resupply in green algae. Abstract: Nitrogen (N) starvation-induced triacylglycerol (TAG) synthesis, and its complex relationship with starch metabolism in algal cells, has been intensively studied; however, few studies have examined the interaction between amino acid metabolism and TAG biosynthesis. Here, via a forward genetic screen for TAG homeostasis, we isolated a Chlamydomonas ( Chlamydomonas reinhardtii ) mutant ( bkdE1α ) that is deficient in the E1α subunit of the branched-chain ketoacid dehydrogenase (BCKDH) complex. Metabolomics analysis revealed a defect in the catabolism of branched-chain amino acids in bkdE1α . Furthermore, this mutant accumulated 30% less TAG than the parental strain during N starvation and was compromised in TAG remobilization upon N resupply. Intriguingly, the rate of mitochondrial respiration was 20% to 35% lower in bkdE1α compared with the parental strains. Three additional knockout mutants of the other components of the BCKDH complex exhibited phenotypes similar to that of bkdE1α . Transcriptional responses of BCKDH to different N status were consistent with its role in TAG homeostasis. Collectively, these results indicate that branched-chain amino acid catabolism contributes to TAG metabolism by providing carbon precursors and ATP, thus highlighting the complex interplay between distinct subcellular metabolisms for oil storage in green microalgae.